P212 Interventions to increase referral to and uptake of pulmonary rehabilitation programmes for people with chronic obstructive pulmonary disease (COPD): a systematic review. (15th November 2016) - Early, F; Wellwood, I; Kuhn, I; Dickerson, T; Ward, J; Brimicombe, J; Deaton, C; Fuld, J
Abstract : Introduction and objectives: Pulmonary Rehabilitation (PR) reduces the number and duration of hospital admissions, readmissions and improves health-related quality of life, e.g. breathlessness and fatigue, in patients with COPD. Despite evidence, guidelines and quality standards, PR is significantly underutilised with under-referral (15% of normative need) and limited uptake (<70% of those referred attend initial assessment) contributing to poor treatment access. We aimed to address the research question: How effective are interventions to improve referral to and uptake of exercise-based pulmonary rehabilitation programmes in patients with COPD when compared to standard care or no intervention? Methods: Systematic review following recognised methods, including all published observational, interventional, qualitative and quantitative studies of interventions specifically intended to increase levels of referral and/or uptake of pulmonary rehabilitation in patients with COPD. Exclusion criteria: individual case studies, conference abstracts and opinion pieces. No date or language restrictions. Search terms included: 'pulmonary rehabilitation' AND 'referral' OR 'uptake' applied to MEDLINE, EMBASE, CINAHL, PsychINFO, ASSIA, BNI, Web of Science and Cochrane Library from inception to June 2016 supplemented by review of reference lists and citation search. Titles, abstracts and full papers were reviewed independently, quality appraised (using Cochrane Collaboration's tool for RCTs and ROBINS-I, AMSTAR) and entered into summary tables. The protocol was registered (PROSPERO) and reported according to PRISMA guidelines. Results: We screened 3217 references, from which 7 papers including 6345 patients and 22 clinicians met inclusion criteria. Most studies (n = 5) were UK based. Designs, interventions and scope of studies were diverse with interventions often part of multifaceted evidence based management of COPD. Examples included computer based prompts at practice nurse review, patient information, financial incentives. Most studies (n = 5) reported improvements in referral or uptake of PR (range 0% – 25% increase), however most had methodological limitations with risk of bias. Due to heterogeneity, studies were not considered combinable and meta-analysis was inappropriate. Conclusions: There is limited evidence for the efficacy of interventions to increase referral and uptake of PR. Existing studies are diverse and further testing using robust methods in various populations and settings is required to optimise access to PR.